Paleocanais no megaleque do rio Taquari: mapeamento e signifcado geomorfológico - Zani, Hiran; Assine, Mario Luis [UNESP] (My University, 2011)
This paper presents the results of the frst systematic mapping of the paleochannel network on the Taquari megafan (Pantanal, Brazil). We used remote sensing data collected by the ASTER sensor, which captures images with 15 m square pixels. A total of 34 scenes, acquired from 2001-2006, were used in the analysis. These data were processed using a decorrelation stretch technique in order to obtain a better visual identifcation of the paleochannels. The mapping procedure began with the overlay of a 1:50.000 IBGE articulation, in order to systematize the extraction of features and to reduce the subjectivity inherent to visual analysis methods. We mapped a total of 33,205 km of paleochannels. The density of these features is related to the relative ages of distinct geomorphological compartments, known as depositional lobes. The mapped features preserve avulsion events that occurred on the megafan. The results suggest that low-magnitude avulsions occur more frequently than larger events.
Paleochannels on Taquari river megafan, Pantanal, Brazil: Their mapping and geomorphological meaning
Keywords: Avulsion; Fuvial geomorphology; Pantanal wetland; Remote sensing